Current antibody-based immunoassay algorithm failed to confirm three late-stage AIDS cases in China: case report - Li, Yan; Zhao, Jin-Kou; Wang, Ming; Han, Zhi-Gang; Cai, Wei-Ping; Zheng, Bo-Jian; Xu, Hui-Fang (Virology journal, 2010)
Immunoassays composed of screening and confirmation are the established algorithm to confirm HIV infection in China, with a Western blot result as the final diagnosis. In this report, three late-stage AIDS patients were initially tested HIV antibody positive using multiple screening kits, but tested indeterminate using Western blot. HIV infection diagnosis was confirmed based on nucleic acid assays, clinic manifestations and epidemiological history. Case A was identified positive at 30 months, using Western blot, Case B at 8 months, and case C remained indeterminate until he died of Kaposi's sarcoma 4 months after HAART. The report indicates that current antibody-based testing algorithms may miss late-stage AIDS patients and therefore miss the opportunity for preventing these cases from further transmission. The report also implies that viral load assays is not easy to be universely applicated in developing country like China although it is helpful in diagnosing complicated cases of HIV infection, so the counselling before and after testing is imperative to the diagnosis of HIV infection and risk behavior survey on the examinee should be as detailed as possible.